New logic in the production of cane sugar in the Zona da Mata pernambucana: transformations land structure to the perpetuation of power relations - Machado, Maria Rita Ivo de Melo; Albuquerque, Mariana Zerbone Alves de (REVISTA NERA, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->The land structure of the Zona da Mata region of Pernambuco is characterized, since the beginning of European colonization, as latifundium and sugar cane plantation. These elements are still composing the region, despite the insertion in the field of new productive forms and working relationships. In this sense, the main objective of this article is understand and analyze the process of transformation of the Zona da Mata de Pernambuco and the consequences to the spatial organization of the region. The 1980s and 90s represent a landmark of temporal attempt to change this land structure on the part of the State forward the social tensions generated in the field. This way, there is a new logic in the production of sugar cane, with the territories reconfiguration, but with the perpetuation of power relations. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->